Feelings in the Field: The Emotional Labour of the Ethnographer - Lo Bosco, Maria Concetta (2021)
Despite the recent theoretical debate over the importance of addressing emotions in fieldwork, most European undergraduate programmes in anthropology still lack methodology courses that specifi cally focus on the emotional impact of doing research. In this article, I draw from my research with activist parents of autistic children in Portugal to explore the affective dimensions of fieldwork experience. In particular, I give an account of how I have dwelled on the emotional challenges that I faced, how these have resulted in vehicles of understanding and affected the analysis of my work as an anthropologist. While fieldwork experience always entails unexpected and surprising emotional challenges, I argue that as anthropologists we can surely benefit from more tailored support networks, safer spaces for discussion, and better pastoral care.